The Influence of Audit Committee, Debt to Equity Ratio, Firm Size, and Audit Tenure on Audit Delay: (Case Study on Energy Sector Companies Listed on the Indonesia Stock Exchange for the Period 2016-2023) - Octaviani, Vina; Febriyanti, Diah (International Journal of Community Service & Engagement, 2025)
This study examines the effect of audit committee, debt to equity ratio (DER), firm size, and audit tenure on audit delay in energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2016-2023. The research sample consisted of 11 companies that met specific criteria, with data analyzed using descriptive tests, normality tests, multicollinearity tests, heteroscedasticity tests, and partial and simultaneous hypothesis tests. The study's results indicate that the audit committee has a significant effect on audit delay, which means that the more audit committee members there are, the less likely an audit delay is. On the other hand, debt to-equity ratio and firm size does not have a significant effect on audit delay. However, audit tenure is proven to have a significant negative effect on audit delay, where the longer the audit tenure, the less likely there is a delay in the audit process. Simultaneously, these four independent variables affect audit delay. The results of this study provide implications that energy sector companies in Indonesia should pay attention to the audit committee's role and audit tenure to speed up the audit process and reduce audit delay